Impact of virtual reality on pain management in transrectal MRI-guided prostate biopsy - Perenic, Emma; Grember, Emilie; Bassard, Sébastien; Koutlidis, Nicolas (Frontiers in Pain Research, 2023)
The beneficial effect of virtual reality (VR) on pain management in the context transrectal MRI-guided prostate biopsy is not well established. However, it remains unclear whether an adjunctive of VR also improves the pain management. The aim of this study was to evaluate the impact of VR as adjunctive in pain management of transrectal MRI-guided prostate biopsy (PB). We retrospectively evaluated the pain intensity incidence in the 153 patients with prostate biopsy indication newly admitted in our hospital since the acquisition of the Healthy mind virtual reality helmet in our hospital on January 19 to January 2021. Baseline characteristics of patients received local anaesthesia with 1% lidocaine periprostatic nerve block (PPNB) (Group SOC, N=78) and patients received VR associated with PPNB (Group VR, N=75) patients were largely similar. One PB with general anesthesia was excluded. The mean pain score at day zero was respectively 3.4 (±2.5) and 2.9 (±2.3) for SOC and VR (p=0.203). However, the mean pain score at day zero was significantly lower in naïve PB patients with VR (2.7 (±2.0)) than in naïve PB patients with SOC (3.8 (±2.5), p=0.012) when patients were stratified in PB status. Similar results were found in Day 3 for the analysis including Naïve-PB patients with SOC vs with VR [0.4 (±2.5) vs 0.2 (±2.0); p=0.023)]. The pain intensity was significantly lower in naïve PB patients with VR than in naïve PB patients with SOC. There was a no side effects about VR occurred and tolerability was excellent.